The use of Internet-based communication by people with autism - Benford, Penny (2008)
Despite having difficulties in the areas of social interaction and communication, the introduction of the Internet seems to have encouraged some high-functioning autistic people to communicate with each other via chat rooms and bulletin boards. The Internet can address the social isolation of autism by improving the potential to find others who have similar experiences. Additionally it may be that, for autistic people, the Internet also offers a comfortable space more suited to their communication style, perhaps one in which their interaction seems less odd. If so, there are possible implications for this group of people in terms of education, employment and social inclusion. However there are risks. Autistic people may be particularly vulnerable to individuals misrepresenting themselves or to the possibility of over-reliance on computer-mediated interaction resulting in an exacerbation of obsessive behaviour and withdrawal from face-to-face interaction. An initial survey, to discover the extent of Internet use among people with autism and investigate their motivations for using it, was carried out, obtaining responses from 138 people with high-functioning autism or Asperger syndrome. Results indicated a high level of computer and Internet use amongst respondents and implied that email was a popular means of communication, more so than face-to-face communication even when interacting with friends. This introductory survey raised issues and questions which were explored in more depth with a subset of the respondents who were interviewed by email about their experiences, motivations and perceptions regarding Internet-based communication. In addition to 19 email interviews, data were also collected from 4 non or reluctant users of the Internet who were sent a series of questions by post. A grounded theory analysis of the data revealed a heightened awareness of communication amongst this group of participants, who offered insights into the process of communication in terms of its component parts and how it breaks down for them. Central to the analysis is a theme of the interviewee as observer, feeling detached to some degree from mainstream interaction and like an outsider. From this perspective participants offered their analysis of the complex process of communication, online and offline as they experienced it, highlighting key aspects of the Internet in relation to their own needs, ones which made it a unique form of communication. Their insights into communication are described in four themes: control, clarity, the role of nonverbal communication and the social role of communication. Additionally the interviewees expressed a sense of liberation that could come with online communication for people with Asperger syndrome/high-functioning autism such that they may interact with others on a more equal basis. This could be empowering but with the sense of liberation there was a risk of losing control over one’s interactions. The interviewees’ perceptions of CMC are explored within a uses and gratifications framework which posits that people use particular communication channels to satisfy their individual needs and motives. By using computer-mediated communication some of the social and communication barriers which contribute to the disability of autism may be broken down.